2006
DOI: 10.1086/505926
|View full text |Cite
|
Sign up to set email alerts
|

Solar Source Regions for3He‐rich Solar Energetic Particle Events Identified Using Imaging Radio, Optical, and Energetic Particle Observations

Abstract: We have identified the sources of six impulsive 3 He-rich solar energetic particle events using imaging radio, optical, and energetic ion and electron data, together with calculated coronal fields obtained from extrapolating photospheric magnetograms using a potential field source surface ( PFSS) model. These events were all studied in 2006 by Wang et al., who identified the particle sources as typically small, flaring active regions lying next to a coronal hole containing Earth-directed open field lines, loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…Type III radio bursts are known to be associated not only with flares, but also with Hα ejecta (Axisa et al 1973), X-ray bright points (Kundu et al 1994(Kundu et al , 1995a, soft X-ray transient brightenings (Nindos et al 1999), and soft X-ray or/and extreme-UV (EUV) jets (Kundu et al 1995b;Raulin et al 1996;Pick et al 2006;Nitta et al 2008;Innes et al 2011;Krucker et al 2011;Klassen et al 2011Klassen et al , 2012Chen et al 2013a,b). Jets that are correlated with type III bursts accompany flaring activity that ranges from weak transient brightenings and subflares (Kundu et al 1995b;Raulin et al 1996;Nitta et al 2008) to M-class flares (Krucker et al 2011;Chen et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type III radio bursts are known to be associated not only with flares, but also with Hα ejecta (Axisa et al 1973), X-ray bright points (Kundu et al 1994(Kundu et al , 1995a, soft X-ray transient brightenings (Nindos et al 1999), and soft X-ray or/and extreme-UV (EUV) jets (Kundu et al 1995b;Raulin et al 1996;Pick et al 2006;Nitta et al 2008;Innes et al 2011;Krucker et al 2011;Klassen et al 2011Klassen et al , 2012Chen et al 2013a,b). Jets that are correlated with type III bursts accompany flaring activity that ranges from weak transient brightenings and subflares (Kundu et al 1995b;Raulin et al 1996;Nitta et al 2008) to M-class flares (Krucker et al 2011;Chen et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Their dimensions may range from about 10 4 km to more than about 10 5 km. They appear most frequently at the edge of active regions and sometimes (Pick et al 2006) close to the border of an active region and a coronal hole.…”
Section: Introductionmentioning
confidence: 99%
“…The impulsive SEP event that occurred on 2002 October 20 gives us an excellent opportunity to carry out this cross disciplinary study. This event had been partially discussed by several other authors (Wang et al 2006b;Pick et al 2006;Wang et al 2011). Unlike previous studies, we derive the solar particle release (SPR) times of SIEEs by considering the instrumental effect and find double injections of electrons at the Sun.…”
Section: Introductionmentioning
confidence: 90%
“…Fe). Traditionally, it was believed that solar flares rather than coronal mass ejections (CMEs) are the acceleration sources of impulsive SEPs, even though some unusual cases appear to be associated with narrow or jet-like CMEs (Wang et al 2006a;Pick et al 2006). Recently, Wang et al (2012) carried out a statistical survey of electron events over one solar cycle and found that only ∼35% of them are related to a reported flare, as compared to that of ∼60% that are related to a CME and to that of ∼50% for which these CMEs are narrow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation